2020
DOI: 10.3390/ijms21093032
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Hippocampal Subfields in Patients with Continuous Remission of Drug-Naive Major Depressive Disorder

Abstract: Objective: Hippocampal volume is reduced in patients with major depressive disorder (MDD) compared with healthy controls. The hippocampus is a limbic structure that has a critical role in MDD. The aim of the present study was to investigate the changes in the volume of the hippocampus and its subfields in MDD patients who responded to antidepressants and subsequently were in continuous remission. Subjects and Methods: Eighteen patients who met the following criteria were enrolled in the present study: the DSM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
(49 reference statements)
0
5
1
Order By: Relevance
“…Our results, taken together with the lack of an association between duration of illness, current or lifetime psychosis, or age at illness onset on any of the subfield volumes, may suggest that putative neurogenic and cell-proliferative effects of antipsychotic medication were not large enough to affect hippocampal subfield volumes. We did not observe any association between subfield volumes and anti-depressant medication, despite previous reports of subfield-volume enlargement in patients with major depressive disorder after selective serotonin reuptake inhibitor or serotonin nor-adrenalin reuptake inhibitor treatment (Katsuki et al, 2020;Maller et al, 2018). This could be due to confounding by other medication use or symptom pathophysiology or severity characteristics within our sample.…”
Section: Medication Effectscontrasting
confidence: 95%
“…Our results, taken together with the lack of an association between duration of illness, current or lifetime psychosis, or age at illness onset on any of the subfield volumes, may suggest that putative neurogenic and cell-proliferative effects of antipsychotic medication were not large enough to affect hippocampal subfield volumes. We did not observe any association between subfield volumes and anti-depressant medication, despite previous reports of subfield-volume enlargement in patients with major depressive disorder after selective serotonin reuptake inhibitor or serotonin nor-adrenalin reuptake inhibitor treatment (Katsuki et al, 2020;Maller et al, 2018). This could be due to confounding by other medication use or symptom pathophysiology or severity characteristics within our sample.…”
Section: Medication Effectscontrasting
confidence: 95%
“… 43 , 44 Regarding structural changes in the hippocampus, subfield-specific changes are considered to exist. 45-47 However, findings on subfield-specific changes in major depressive disorders are inconsistent because they may depend not only on medication use 48 and illness duration 49 but also on the diversity of segmentation protocols. 10 Regarding hippocampal network abnormality in major depressive disorder, recent studies have focused on the connectivity of specific hippocampal subfields with the rest of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data suggests that depression, particularly late-life depression, can also be a risk factor for AD. 3 Two prior studies 19,20 reported significant volume change in some subfield hippocampal regions in MDD patients with some specific conditions, such as recurrent episode of depressive symptom (decreased volume as the number of prior episodes increased) 19 , or continuous remission of drug-naive disease (increased volume in MDD patients who were in remission at least 6 months). Concerning our result, there was no statistically significant difference in volumetric analysis compared between first-diagnosed and untreated MDD and either MCI or HOA subjects.…”
Section: Discussionmentioning
confidence: 99%